Atomically dispersed Co-Cu dual active sites in carbon networks as an efficient oxygen electrocatalyst - Sinha, Nibedita; Das, Chandni; Pal, Santanu; Urkude, Rajashri R.; Ahmed, Tanbir; Ghosh, Biplab; Roy, Poulomi (Dalton Transactions, 2025)
Single-atom metal-based electrocatalysts offer extended advantages by maximizing the utilization of active sites but often suffer from complex synthesis processes and low-density metal loading. The present work showcases a strategic design for integrating highly dense cobalt-copper dual atoms dispersed on a nitrogen-rich porous carbon network (CoCu-NGC). The atomically dispersed CoCu-NGC outperforms the ORR and OER activities of their single metallic counterparts (Co-NGC or Cu-NGC) and conventional noble-metal based electrocatalysts (Pt/C and RuO2). Benefitting from the electronic modulation in the dual SAC system, the CoCu-NGC displayed outstanding bifunctional performance with low Delta E values of 0.69 V in freshwater and 0.78 V in seawater, highlighting it as a potential alternative to the costly state-of-art electrocatalysts.

Enhanced electrocatalytic performances of NiCr layered double hydroxides by oxalate intercalation in anion exchange membrane water electrolysis - Pal, Santanu; Sinha, Nibedita; Das, Chandni; Chauhan, Inderjeet; Ahmed, Tanbir; Roy, Poulomi (ACS Applied Materials & Interfaces, 2025)
Layered double hydroxides (LDHs) have attracted much attention these days in the field of water electrolysis due to easy modulation in their layered structure and properties. Herein, NiCr-LDH has been developed, and its interlayer spacing has been considerably increased by oxalate intercalation. Such increased interlayer spacing allows easy access of hydroxides to a large number of electroactive sites and thereby boosts the electrocatalytic performances both for oxygen and hydrogen evolution reactions. Being very active toward both the electrocatalytic reactions, the oxalate-intercalated NiCr-LDH was further explored in an alkaline anion exchange membrane water electrolyzer (AEMWE), achieving 800 mA cm-2 at 1.88 V cell voltage at an operating temperature of 60 degrees C. In fact, the electrolyzer efficiency has been determined to be as high as 69.66%, and the calculated H2 production cost was found to be \$0.97 per gasoline-gallon equivalent, which is well below the targeted cost by the Department of Energy, USA. The electrocatalyst was also examined in harsh alkaline media, like highly saline or seawater, which also indicated its ability to carry out sustainable seawater electrolysis, restricting chlorides to a great extent. Interestingly, post-electrolysis characterization reveals the fact that oxalate decomposition aided carbonate formation within interlayers of NiCr-LDH, and high affinity toward hydroxides is responsible for restricting chlorides during the electrolysis process, apart from the great electrocatalytic activity.
Keywords: Anion exchange; hydrogen production; interlayerspacing; Layered double hydroxide; Sustainable; water electrolyzer

NiFeMo layered triple hydroxide and MXene heterostructure for boosted oxygen evolution reaction in anion exchange membrane water electrolysis - Pal, Santanu; Chaturvedi, Ekta; Das, Chandni; Sinha, Nibedita; Ahmed, Tanbir; Roy, Poulomi (Nanoscale, 2025)
Efficient, low cost and stable electrocatalysts are highly desirable for overcoming the sluggish kinetics of the oxygen evolution reaction (OER) in alkaline water electrolysis for hydrogen production. Interfacial engineering of heterostructures is quite beneficial for improving charge transfer efficiency at the interface. In this context, heterostructures of layered triple hydroxides (LTHs) and MXenes have shown great potential as OER electrocatalysts owing to their 2D-2D structure and unique physiochemical properties. Coupling LTHs with MXenes can potentially enhance their conductivity and stability, thereby boosting OER activity. In this study, we report a heterointerface between NiFeMo-LTH on Ti3C2Tx MXene, which exhibited superior catalytic activity and stability in alkaline freshwater and seawater, reducing the activation energy. Importantly, the heterostructure achieved a current density of 100 mA cm-2 at the cost of 292 mV and 340 mV overpotentials in alkaline saline water and real seawater, respectively, and showed robustness over 100 h without hypochlorite formation in alkaline real seawater, exhibiting corrosion-resistant behaviour. Moreover, NiFeMo-LTH/MXene explored in alkaline anion exchange membrane water electrolyzer (AEMWE) achieved a current density of 750 mA cm-2 at 2.16 V cell voltage at an operating temperature of 60 degrees C with an energy efficiency of 60.5%. Raman analysis and XPS analysis post stability test demonstrated easy electron transfer from LTH to MXene at the heterointerface, leading to the formation of NiOOH electroactive species that facilitated the OER activity.

Amorphous vanadium-doped iron borate/tetraboride hybrid as an efficient electrocatalyst for the oxygen evolution reaction - Ahmed, Tanbir; Pal, Santanu; Sinha, Nibedita; Das, Chandni; Roy, Poulomi (Dalton Transactions, 2026)
The design of an effective electrocatalyst as a replacement for a conventional expensive electrocatalyst for facilitating the sluggish oxygen evolution reaction (OER) at the anode has been identified as an effective way to make hydrogen production economical. Herein, we have developed a unique combination of iron borate and iron tetraboride (Fe-BO/FeB) by a facile chemical reduction process. The optimum vanadium doping further led to the transformation of Fe-BO/FeB into an amorphous form, which is believed to be very beneficial for the OER mechanism. The developed electrocatalyst needs overpotentials of 215 mV and 256 mV in alkaline 1 M KOH electrolyte to achieve current densities of 10 and 100 mA cm-2, respectively, and it also shows stability over 48 h, maintaining a high current density of 200 mA cm-2. Enhanced performances were also confirmed by smaller activation energies for the optimized sample compared with a pristine electrocatalyst.